Posture Improvement and Stretching Treatment Based on Participatory Ergonomic Decrease Risk of Work Posture and Low Back Pain Intensity on Brick Workers in Kupang, NTT - Jacob M Ratu (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Low Back Pain (LBP) is widely experienced by many brick workers who generally carry out repeated physical activities of lifting-and-carrying with non-ergonomic postures. Such condition can increase the risk of work posture and LBP intensity which if continued can disrupt the continuity of production, increase the risk of injury, and reduce worker productivity. Simultaneous intervention of posture improvement and stretching is conducted with the aim of reducing the risk of work posture and LBP intensity. This research was a quasi-experimental study using pre and post test design. Nineteen males brick workers from the brick production business unit sample in Kupang City who met the eligibility criteria participated in this study. They were determined as samples using purposive sampling technique. Simultaneous improvement of posture and stretching treatment is the selected intervention model agreed upon by researchers, workers and business owners to reduce the risk of work posture and LBP intensity for 5 weeks. The risk of work posture was measured by Rapid Entire Body Assessment (REBA) while LBP intensity was measured using a modified Oswestry questionnaire. Five main activities were measured for LBP intensity i.e. lifting, standing, sitting, walking, social life and sleeping. Measurements the risk level of work posture and LBP intensity were taken before and after the intervention. The data were analyzed by paired t test with a significance level of 5%. The results showed that posture improvement and stretching treatment reduced the risk level of brick workers' work posture from the average score of 9.25 to 5.0 or a decrease of 45.95% and reduced the intensity of LBP from 3.53 to 2.54 or a decrease 28.05%. The highest decrease in the pain intensity was found during sleep i.e. 39.19% and the lowest during lifting activity i.e. 15%. The conclusion is the improvement of posture and stretching treatment base on participatory ergonomic can reduce the risk of work posture and LBP intensity of brick workers.